As referências da formação inicial na representação dos licenciandos em ciências biológicas da Universidade Estadual de Ponta Grossa - Tolentino, Patricia Caldeira (2010)
This research aims to clarify how the formation field of the Biological Sciences Graduation Course of the State University of Ponta Grossa sets and how the routines and practices experienced in the graduation present in the representation of the undergraduates. It was applied a free association Word questionnaire and closed and opened questions to 138 undergraduates from 1st , 2nd, 3rd and 4th years of the Biological Sciences Graduation Course from the afternoon and night shifts. It was used a quail-quantitative approach, and the collected data were submitted to processing through the use of data analysis software EVOC, SIMI, Alceste and SPSS. The data were interpreted using the Theory of Social Representations from Serge Moscovici articulated to Pierre Bourdieu´s habitus and field concepts. From these data,and from such concepts are indications that students entering the course have convictions about the training at undergraduate, but in the final two years the conflicts of identity arise. This presentation summarizes in the narrative of undergraduates the ownership of the circulating elements in this social space, legitimizing the hierarchical positions of biological knowledge and educational knowledge. These situations must be discussed in the training process, because they produce obstacles to the incorporation of the necessary structures in the formation of identity references to the constitution of the teaching profession.